Cover. (February 2017) - Unknown
Abstract : Front cover : The cover image, by Fang K. Du et al., of the evergreen oak Quercus aquifolioides on the tree line in Tibet, is based on the Original Article Phylogeography of Quercus aquifolioides provides novel insights into the Neogene history of a major global hotspot of plant diversity in south‐west China, DOI:10.1111/jbi.12836 . Photo Credit: Fang K. Du.